Active Physical Activity Patterns Are Associated With Improved Quality of Life and Depression Status in Taiwanese Women With Metabolic Syndrome. Issue 6 (November 2019) - Chiang, Li-Chi; Chiang, Shang-Lin; Tzeng, Wen-Chii; Lee, Meei-Shyuan; Hung, Yi-Jen; Lin, Chia-Huei
Abstract : Background: Metabolic syndrome (MetS), health-related quality of life (HRQL), and depression status are independently associated with cardiac health. Therefore, understanding the associations between MetS, HRQL, and depression status and determining factors related to improved HRQL and depression status in people with MetS may help in cardiovascular disease prevention. Objective: The aim of this study was to examine whether there are differences in HRQL and depression status between Taiwanese women with and without MetS and whether physical activity patterns are associated with HRQL and depression status in this population. Methods: A cross-sectional study of 326 Taiwanese middle-aged and older women (≥40 years) was conducted. Metabolic syndrome was determined based on the National Cholesterol Education Program Adult Treatment Panel III definition. Health-related quality of life and depression status were collected using the Short Form 36 Health Survey and Beck Depression Inventory. Univariate and multivariate linear regression analyses were conducted. Results: Women with MetS had lower HRQL ( P < .001) and higher depression status ( P = .002) than those without MetS. Participants with active physical activity patterns had higher HRQL ( P < .001) and lower depression status ( P = .046) than those with sedentary patterns. Among women with MetS, those with active physical activity patterns had higher HRQL ( P = .001) and lower depression status ( P = .007) than those with sedentary patterns. Conclusions: Metabolic syndrome is related to lower HRQL and higher depression status in women 40 years and older. Active physical activity patterns are associated with better HRQL and reduced depression status in middle-aged and older women (≥40 years) with MetS.